Development and assessment of a block machine for volleyball attack training. (2nd November 2017) - Sato, Kosuke; Watanabe, Keita; Mizuno, Shuichi; Manabe, Masayoshi; Yano, Hiroaki; Iwata, Hiroo
Abstract: This study presents a system that consists of three machines to imitate the motion of top volleyball blockers. In a volleyball match, it is essential to improve the hitting percentage of each spiker in order to score by spiking. Iterative spiking training is required for increasing the hitting percentage. Therefore, we develop a block machine system that can be continuously used in an actual practice field for improving attack practice. Each machine is equipped with five degrees of freedom to achieve the required operating speed and mechanical strength. The machine performs high-speed movements on 9000 mm rails that are arranged parallel to the volleyball net. In addition, an application with a graphical user interface enables a coach to manipulate these machines. It enables the coach to control block motions and change the parameters such as the machines' position and operation timing. We evaluate the feasibility of the proposed block form through practical use of the system in the practice field and confirm that the system has potential for improving attack efficiency. Graphical Abstract: